2021
DOI: 10.18332/tid/132148
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation advice and quit attempts in South Africa between 2007 and 2017: A cross-sectional study

Abstract: daily smoking has decreased from 42% to 37% among men, and 11% to 8% among women 6,7. However, smoking rates remain unacceptably high among the Colored (mixed ancestry) population, where it is reported to be 49.3% among men and 38.1% among women, in 2017. In addition, an estimated 51.2% and 10.4% of tobacco and non-tobacco users, respectively, are still regularly exposed to secondhand smoke (SHS) at home or outside of home. In 2010, the Conference of Parties (CoP) to the WHO Framework convention on tobacco con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous studies have reported a significant reduction in the prevalence of tobacco use in South Africa (SA) 15,16 , following the introduction of the Tobacco Products Control Act 83 of 1993 (amended 2008) 17 . However, this reduction in prevalence has stabilized with no change in quitting behavior over the same period 18 , and recent increases in tobacco use have been reported between 2008 and 2011 among South Africans 13,19 . The re-bound and increase in tobacco use prevalence have been attributed to the marketing and social acceptance of novel and re-emerging tobacco/ nicotine products such as e-cigarettes and waterpipe tobacco which come in exotic flavors, and promoted for use in social settings 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a significant reduction in the prevalence of tobacco use in South Africa (SA) 15,16 , following the introduction of the Tobacco Products Control Act 83 of 1993 (amended 2008) 17 . However, this reduction in prevalence has stabilized with no change in quitting behavior over the same period 18 , and recent increases in tobacco use have been reported between 2008 and 2011 among South Africans 13,19 . The re-bound and increase in tobacco use prevalence have been attributed to the marketing and social acceptance of novel and re-emerging tobacco/ nicotine products such as e-cigarettes and waterpipe tobacco which come in exotic flavors, and promoted for use in social settings 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they can provide continued support to prevent relapse (Devonish et al 2022 ). Primary care physicians, dentists, nurses and other health professionals have been involved in smoking cessation interventions in the United States, Europe, Australia, South Africa and other countries (Ayo-Yusuf & Omole 2021 ; Gajendra, McIntosh & Ghosh 2023 ; Mersha et al 2022 ). Several evidence-based guidelines are available to assist health professionals with tobacco cessation interventions (Verbiest et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current literature suggests that despite evidence-based guidelines and recommendations being available nationally and internationally, there is still a gap between evidence and practice when assessing tobacco use and supporting patients to quit (Ayo-Yusuf & Omole 2021 ; Jradi 2017 ; Tadzimirwa et al 2019 ). In the GATS-SA survey in 2021, 65.7% of current South African smokers expressed an interest in quitting, but only 42.9% of smokers who visited their physician in the past 12 months received cessation advice (SAMRC 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review on tobacco cessation interventions in LMICs report a shortage of evidence on smoking cessation in context of African countries [ 21 ], unavailability of representative data on smoking cessation is regarded as one of the challenges towards effective smoking cessation strategies in Africa [ 22 ]. While few surveys reported a lack of awareness and access to smoking cessation support among vulnerable populations [ 23 , 24 ], surveys of smoking cessation usually cover urban, selected regions or certain population subgroups and are rarely nationally representative. Therefore, we conducted this study with the following objectives.…”
Section: Introductionmentioning
confidence: 99%